Sources of welfare disparities across and within regions of Brazil : evidence from the 2002-03 household budget survey - Skoufias, Emmanuel (Policy research working paper, 2008)
"Brazil's inequalities in welfare and poverty across and within regions can be accounted for by differences in household attributes and returns to those attributes. This paper uses Oaxaca-Blinder decompositions at the mean as well as at different quantiles of welfare distributions on regionally representative household survey data (2002-03 Household Budget Survey). The analysis finds that household attributes account for most of the welfare differences between urban and rural areas within regions. However, comparing the lagging Northeast region with the leading Southeast region, differences in returns to attributes account for a large part of the welfare disparities, in particular in metropolitan areas, supporting the presence of agglomeration effects in booming areas. "--World Bank web site